2013
DOI: 10.1590/s1519-69842013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Arthropod edaphic fauna in preserved and managed with pasture areas in Teresina-Piauí-Brazil

Abstract: The soil fauna plays an important function over the processes of organic matter decomposition, nutrient cycling, ground aeration and fertility. Thus, studies on the composition and structure of such communities are important, considering moreover the lack of information in different regions of Brazil and mainly related to the state of Piauí. This study aimed to evaluate the density and diversity of the soil arthropod fauna in a Cerrado area in preservation conditions and in a pasture area. Both are situated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
2
6
1
2
Order By: Relevance
“…This result suggests that this agricultural practice degraded the habitat for litter-dwelling species and at the same time, created an open and dry habitat that favored the Formicidae (Graham et al, 2004). A similar finding was found by Luz et al (2013), who reported a higher frequency of Formicidae in managed areas than in native forests in Northeast Brazil.…”
Section: Discussionsupporting
confidence: 78%
“…This result suggests that this agricultural practice degraded the habitat for litter-dwelling species and at the same time, created an open and dry habitat that favored the Formicidae (Graham et al, 2004). A similar finding was found by Luz et al (2013), who reported a higher frequency of Formicidae in managed areas than in native forests in Northeast Brazil.…”
Section: Discussionsupporting
confidence: 78%
“…However, the slope of the species accumulation curve in early samplings shows that the data sufficiently represent the arthropod community of this Cerrado fragment. Our results are relatively higher in order richness and abundance of specimens when compared to other studies that collected arthropods in Cerrado using pitfalls (diniz & MOraiS 2008;vaScOncelOS et al 2009;uehara-PradO et al 2010;luz et al 2013).…”
Section: Discussioncontrasting
confidence: 76%
“…Quando estes processos naturais desaparecem, os custos ambientais e socioeconômicos podem ser significativos (ALTIERI et al, 2003). Levando em consideração as informações acima citadas, Luz et al, (2013) em levantamento da fauna de artrópodes edáficos realizado com armadilhas de bandeja d'água, observaram que as formigas foram as mais abundantes representantes da ordem Hymenoptera em áreas sob interferência antrópica e áreas preservadas, diminuindo significativamente o número de insetos capturados em áreas preservadas.…”
Section: Insetos Coletados Na Estação Secaunclassified
“…Já as moscas domésticas ocorreram em maior número devido a proximidade das residências rurais e criações de animais domésticos. Em avaliação da fauna de artrópodes edáficos em áreas de pastagem com uso de armadilhas d'água, a família Sarcophagidae apresentou-se mais representativa em termos de indivíduos capturados (LUZ et al, 2013), o que demostra que em áreas agrícolas de maior diversidade de cultivo e atividades agropecuárias atraem indivíduos com uma maior amplitude com relação aos hábitos alimentares.…”
Section: Insetos Coletados Na Estação Secaunclassified